Analysis of Three Antecedent Dimensions of Service Towards Consumer's Trust and Their Impact on Post-Purchase Behavior - Dewanti, Retno; Teoh, Wendy; Wati, Yulia; Rahayu, Rahayu (Journal the Winners: Economics, Business, Management, and Information System Journal, 2011)
In the last few years retail industry in Indonesia has been grown rapidly by three main factors, namely economic, demographic and socio-cultural. If a retail business can gain success in Malaysia, it may not gain the same success in Indonesia. A research is conducted using associative analysis by correlation test with path analysis technique and Pearson Product Moment correlation. The results of this research show that three antecedents of service variables – interaction quality, the quality of physical environment, and outcome quality – are related to each other and simultaneously influence consumer’s trust. Regarding to the partial analysis, it is found that the quality of physical environment and consumer’s trust has significant effects on post-purchase behavior. Path analysis shows that three antecedents of service indirectly contribute to consumer post-purchase behavior through consumer’s trust. However, the outcome quality provides the largest contribution on it.